2009
DOI: 10.5194/acp-9-207-2009
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurements of speciated atmospheric mercury and the identification of source regions in the Mexico City Metropolitan Area

Abstract: Abstract. In order to expand the currently limited understanding of atmospheric mercury source-receptor relationships in the Mexico City Metropolitan Area, real time measurements of atmospheric mercury were made at a downtown urban site, and a rural site on the outskirts of Mexico City, during March 2006. Numerous short-lived increases in particulate mercury (PHg) and reactive gaseous mercury (RGM) concentrations were observed at the urban site during the 17 day study, and less frequent increases in gaseous e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 66 publications
1
46
1
Order By: Relevance
“…Similarly, higher CWT values for GEM in the Atlantic Ocean all year round suggested that the evasion of GEM from the ocean was a potential source of GEM in Nova Scotia (Cheng et al, 2013b). CFA results for the Mexico City sites indicated that the sites were impacted by known Hg point sources, such as cement and chemical production and paper and cardboard manufacturing, and by potential unregistered sources and volcanic emissions (Rutter et al, 2009).…”
Section: Cfa Rtwc and Cwt Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Similarly, higher CWT values for GEM in the Atlantic Ocean all year round suggested that the evasion of GEM from the ocean was a potential source of GEM in Nova Scotia (Cheng et al, 2013b). CFA results for the Mexico City sites indicated that the sites were impacted by known Hg point sources, such as cement and chemical production and paper and cardboard manufacturing, and by potential unregistered sources and volcanic emissions (Rutter et al, 2009).…”
Section: Cfa Rtwc and Cwt Resultsmentioning
confidence: 98%
“…CFA, RTWC, and CWT have been used to identify potential sources of TGM and speciated atmospheric Hg contributing to multiple sites in New York (Han et al, 2007), Mexico City (Rutter et al, 2009), Milwaukee, Wisconsin (de Foy et al, 2012; and Dartmouth, Nova Scotia (Cheng et al, 2013b). The New York and Milwaukee sites in the Great Lakes region and the Nova Scotia site identified industrial areas in Ohio and the eastern US as potential Hg sources (Han et al, 2007;de Foy et al, 2012;Cheng et al, 2013b).…”
Section: Cfa Rtwc and Cwt Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the results are plotted on a map, these models illustrate potential source areas affecting a receptor site. There are several variations of TSMs that have been applied to speciated atmospheric Hg studies: Potential Source Contribution Function (PSCF) (Han et al, 2005(Han et al, , 2007Abbott et al, 2008;Choi et al, 2008;Xu and Akhtar, 2010;Fu et al, 2011), Gridded Frequency Distributions (GFD) (Weiss-Penzias et al, 2011;Gustin et al, 2012), Concentration Fields Analysis (Rutter et al, 2009) or Concentration-Weighted Trajectory (CWT), and Residence Time Weighted Concentration (RTWC) (Han et al, 2007). They all involve counting the frequency of back trajectory segment endpoints in grid cells that make up the geographical domain of interest for the receptor site.…”
Section: Introductionmentioning
confidence: 99%